Correction and compensation of an airborne fluxgate magnetic tensor gradiometer. Issue 5 (1st October 2018) - Sui, Yangyi; Miao, Hongsong; Zhou, Zhijian; Luan, Hui; Wang, Yanzhang
Abstract : An airborne fluxgate magnetic tensor gradiometer is built on fluxgates to measure directional derivatives of the magnetic field. It has been used to carry out many geophysical exploration programs quickly and efficiently. However, two key issues greatly reduce the data quality of a tensor gradiometer. One is that the fluxgate magnetic tensor gradiometer suffers various errors, such as scale drift, non-orthogonality, misalignment, zero offset, dynamic, and nonlinear errors of individual fluxgates, along with differences between characteristics of fluxgates. The other is that manoeuvring an aircraft flying in the geomagnetic field can generate magnetic interference effects on a tensor gradiometer. Regarding the common airborne fluxgate magnetic tensor gradiometer that has a cross-shaped structure, we have proposed the magnetic interference model of the aircraft and the error model of a single fluxgate. Then we have seamlessly combined these two models into the unified calibration model of a tensor gradiometer by a recursive method. Finally, we have simultaneously determined the correction coefficients and the magnetic properties of the aircraft by a calibration flight at high altitude in an area of low magnetic gradient. We have evaluated the performance of the proposed method through simulation and actual flight results using a microlight aircraft. The root-mean-square noise of each component has reached the level of less than 1.5 nT/m, and the improvement ratios are from 4096 to 17444 in terms of the measured field data of tensor components. The proposed method reduces the reliance of the installation on the aircraft and can easily be applied to other tensor gradiometers, such as airborne superconducting magnetic tensor gradiometers. Abstract : In this paper, the correction coefficients of a fluxgate magnetic tensor gradiometer and the magnetic properties of an aircraft are determined. A recursive method is used to combine the magnetic interference model and the error model into a unified calibration model. The method is significant as there will be a greater use of airborne magnetic tensor gradiometers using a wide range of aircraft.